Elastic properties of B19’ structure of NiTi alloy under uniaxial and hydrostatic loading from first principles - Sestak, P.; Cerny, M.; Pokluda, J. (Проблемы прочности, 2008)
The uniaxial and hydrostatic deformations of martensitic structure B19’ of NiTi shape memory alloy are studied using first-principles calculations. The bulk and Young’s moduli and the theoretical strength under uniaxial tension and hydrostatic loading are computed from crystal response to applied deformations. The behavior of angle β of the B 19’ structure was investigated along the whole deformation path. The computed values of Young’s moduli are compared with available experimental results. The results obtained complement and extend the already known characteristics of NiTi alloy.